PENGEMBANGAN MODUL MATERI BANGUN DATAR BERBASIS ETNOMATEMATIKA MELAYU KUANSING DI SEKOLAH DASAR - Suci Azliyanti Maha Putri; Zetra Hainul Putra; Mahmud Alpusari (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Ethnomathematics-based mathematics learning is a learning innovation that aims not only to learn mathematical content but also to preserve local wisdom that exists in an area. However, many elementary school teachers, especially Kuantan Singingi district, Riau Province have not implemented ethnomathematics-based mathematics learning because its resources are not yet available. Therefore, this study aims to develop a flat shape material module based on Kuansing Malay ethnomathematics. This research uses the ADDIE model development research method with stages, namely: Analysis, Design, Development, Implementation and Evaluation. Data collection and analysis was carried out by testing validity with experts and practicality with elementary school students. The results of the study show that the Malay Kuansing ethnomathematics-based flat shape material module meets the valid and practical criteria with a percentage of material expert validators of 94.45%, media experts of 90.17%, language experts of 91.67%, and a percentage of practicality by teachers of 96.25% and students of 92.5%. This can be concluded that the flat shape material module based on Kuansing Malay ethnomathematics meets the valid and practical criteria so that it is suitable for use in mathematics learning in elementary schools.